2011
DOI: 10.1016/j.jaci.2010.12.1083
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunotherapy for peanut allergy: Clinical and immunologic evidence of desensitization

Abstract: Background-There are no treatments currently available for peanut allergy. Sublingual immunotherapy is a novel approach to the treatment of peanut allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
309
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(329 citation statements)
references
References 24 publications
13
309
2
5
Order By: Relevance
“…Oral immunotherapy (OIT) and sublingual immunotherapy (SLIT) studies suggest that an older age at the start of treatment may result in more difficulty achieving desensitization, as success rates tended to be higher in studies that included primarily younger children. [22][23][24] Furthermore, in 2 studies that included children with a history of anaphylaxis, lower success rates for desensitization were observed in comparison to studies that excluded those with a history of anaphylaxis. [25,26] Subjects in our study were older, with a median age of 16 years, and over a third had a history of anaphylaxis, thus our study population may need optimized doses and prolonged treatment to impact their established allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Oral immunotherapy (OIT) and sublingual immunotherapy (SLIT) studies suggest that an older age at the start of treatment may result in more difficulty achieving desensitization, as success rates tended to be higher in studies that included primarily younger children. [22][23][24] Furthermore, in 2 studies that included children with a history of anaphylaxis, lower success rates for desensitization were observed in comparison to studies that excluded those with a history of anaphylaxis. [25,26] Subjects in our study were older, with a median age of 16 years, and over a third had a history of anaphylaxis, thus our study population may need optimized doses and prolonged treatment to impact their established allergy.…”
Section: Discussionmentioning
confidence: 99%
“…(29;30) In an ongoing, single-center placebo controlled clinical trial, Kim et al evaluated peanut SLIT in pediatric subjects. (25) Similar to the current study, they utilized a 1:1 randomization scheme, assigned a 2mg per day maintenance dose, and performed a per-protocol interim analysis of desensitization as the primary efficacy end point, measured by a 2.5g peanut protein (5g peanut powder) DBPCFC after 52 weeks of therapy. Interestingly, both studies (1) met their primary statistical end point; (2) showed significant variation in the clinical desensitization effect size; (3) demonstrated evidence of skin test (i.e., mast cell) suppression; and (4) observed increases in allergen-specific IgG4 levels among actively treated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…(22)(23)(24) SLIT has also been utilized for treatment of allergy to several foods including kiwi, hazelnut, peach, milk and most recently peanut. (25)(26)(27)(28)(29)(30)(31) In this study we examined the clinical effects and safety profile of peanut SLIT in what is to date the first multicenter, randomized, placebo-controlled trial. We present data on the primary end point of the study, the percentage of desensitized subjects, as well as several secondary end points including tolerability of up-dosing, differences in response between treatment dosing arms, safety profile, and immunologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…& In peanut-allergic subjects, Kim et al [71] found decreases in peanut SPT wheal size, basophil activity, peanut-specific IgE, and IL-5 levels after 12 months of peanut SLIT. There were significant increases in peanut-specific IgG4 but non-significant increases in numbers of Tregs.…”
Section: Sublingual Immunotherapymentioning
confidence: 99%